The Effect Of Sleep Hygiene Activity Therapy On Sleep Quality In The Elderly - Sonhaji Sonhaji; Ni Nyoman Maryaningtyas Adinatha; Wiji Setiani (Jurnal Smart Keperawatan, 2022)
Hypertension is a health problem experienced by some people through the aging process, this results in an increased risk of cardio-cerebrovascular morbidity, such as myocardial infarction, heart failure, and stroke. The purpose of the study was to determine the effectiveness of the application of education on rest and sleep patterns on reducing blood pressure in the elderly. This research was Quantitative method with pre-experimental design. The sampling technique used probability sampling with simple random sampling method, the number of samples that matched the inclusion and exclusion criteria were 39 elderly people in Mondoteko Village, Rembang City, the analysis used a paired t-test. The results showed that the systolic blood pressure before being given the application of educational therapy for rest and sleep patterns (intervention) was 169.49 mmHg with a standard deviation of 12.34 and after being given the intervention was 94.36 mmHg with a standard deviation of 5.52. The p-value of systolic blood pressure was 0.001. Diastolic blood pressure before the intervention was 129.23 mmHg with a standard deviation of 7.39. The diastolic value after the intervention was 76.41 mmHg with a standard deviation of 6.277. The p-value of diastolic blood pressure is 0.001. There is an effectiveness of the application of educational therapy on rest and sleep patterns to decrease systolic and diastolic blood pressure in the elderly in Mondoteko Village, Rembang. Keywords: educational therapy; rest and sleep; blood pressure; elderly ABSTRACT Lansia merupakan kondisi dimana seseorang akan mengalami kemunduran secara alamiah yaitu tubuh yang akan mengalami penuaan dan ditandai dengan terjadinya perubahan bentuk fisik serta fungsi tubuh yang mulai menurun. Perubahan pola tidur akibat proses penuaan lansia mempengaruhi kualitas tidur lansia antara lain kesulitan memulai tidur, kesulitan mempertahankan tidur, dan bangun terlalu pagi. Sleep hygiene penting dalam intervensi munculnya kasus insomnia yang  terjadi pada orang lanjut usia dengan angka prevalensi diperkirakan sebesar 13- 47% dengan proporsi sekitar 50-70% terjadi diusia diatas 65 tahun. Tujuan mengatahui tingkat pengaruh terapi sleep hygiene terhadap kualitas tidur lansia. Metode penelitian bersifat deskriptif kuantitatif dengan menggunakan desain quasi eksperimen pre-post test one group design. Teknik sampling adalah purposive sampling dengan jumlah sampel ≥ 16 responden. Instrument penelitian menggunakan kuesioner dengan uji analisa uji paired T Test. Hasil menunjukkan sebelum dilakukan terapi sleep hygine nilai mean gangguan tidur berat adalah 15,69 pada 93,8% responden dan setelah dilakukan terapi sleep hygine nilai mean adalah 10,00 (gangguan tidur ringan) pada 87,5% responden. Nilai p value 0,000 yang artinya ada pengaruh terapi aktivitas sleep hygiene terhadap kualitas tidur lansia. Kata Kunci : lansia; sleep hygiene; kualitas tidur